Cas9/AAV9-Mediated Somatic Mutagenesis Uncovered the Cell-Autonomous Role of Sarcoplasmic/Endoplasmic Reticulum Calcium ATPase 2 in Murine Cardiomyocyte Maturation - Lin, Junsen; Chen, Zhan; Yang, Luzi; Liu, Lei; Yue, Peng; Sun, Yueshen; Zhao, Mingming; Guo, Xiaoling; Hu, Xiaomin; Zhang, Yan; Zhang, Hong; Li, Yifei; et al. (Frontiers in Cell and Developmental Biology, 2022)
Sarcoplasmic/endoplasmic reticulum calcium ATPase 2 (SERCA2) is a key player in cardiomyocyte calcium handling and also a classic target in the gene therapy for heart failure. SERCA2 expression dramatically increases during cardiomyocyte maturation in the postnatal phase of heart development, which is essential for the heart to acquire its full function in adults. However, whether and how SERCA2 regulates cardiomyocyte maturation remains unclear. Here, we performed Cas9/AAV9-mediated somatic mutagenesis (CASAAV) in mice and achieved cardiomyocyte-specific knockout of Atp2a2, the gene coding SERCA2. Through a cardiac genetic mosaic analysis, we demonstrated the cell-autonomous role of SERCA2 in building key ultrastructures of mature ventricular cardiomyocytes, including transverse-tubules and sarcomeres. SERCA2 also exerts a profound impact on oxidative respiration gene expression and sarcomere isoform switching from Myh7/Tnni1 to Myh6/Tnni3, which are transcriptional hallmarks of cardiomyocyte maturation. Together, this study uncovered a pivotal role of SERCA2 in heart development and provided new insights about SERCA2-based cardiac gene therapy.